Image Caption Generation and Object Detection via a Single Model - Aghasi S. Poghosyan (Изд-во НАН РА)
Automated semantic information extraction from the image is a di±cult task. There are works which can extract image caption or object names and their coordinates. This work presents a merged single model of object detection and automated caption generation systems. The final model extracts from image caption and object coordinates with their names without losing accuracy according to initial models.
Keywords: Mathematics